2019
DOI: 10.1590/1519-6984.179526
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the phytochemical profiles of five native plant species in two different forest formations

Abstract: The expression of chemical compounds by individual plants of the same species in different locations may be affected by abiotic factors resulting in differences in the production of allelopathic compounds. The objective of this study was to compare the phytochemical profiles of plant species from two different forest formations in the state of Paraná, Brazil. The forest formations were Seasonal Semideciduous Forest (SSF) and Lowland Ombrophilous Dense Forest (LODF), and the five study species were Jacaranda mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Although the IC 50 value of BHT was lower than that of the extract, the results showed that the plant possesses antioxidant activity. The chemical compounds produced by plants can be altered by several abiotic factors, which interfere in the expression of allelopathic compounds (Pilatti et al, 2019). It is suggested that the antioxidant activity may be related to the presence of phenolic compounds, especially tannins that have antioxidant activity, and they were identified in the present study.…”
Section: Discussionmentioning
confidence: 60%
“…Although the IC 50 value of BHT was lower than that of the extract, the results showed that the plant possesses antioxidant activity. The chemical compounds produced by plants can be altered by several abiotic factors, which interfere in the expression of allelopathic compounds (Pilatti et al, 2019). It is suggested that the antioxidant activity may be related to the presence of phenolic compounds, especially tannins that have antioxidant activity, and they were identified in the present study.…”
Section: Discussionmentioning
confidence: 60%
“…The main constituents of essential oils S. polycephalum are α-bergamotene (5.57%), nerolidol (10.84%), trans-caryophyllene (1.11%), trans-farnesyl acetate (0.72%). In general, the expression of compounds by individual plants of the same species at different location can be influenced by ecological factors (Pilatti et al, 2019).…”
Section: Results and Discussion Chemical Compound Analysismentioning
confidence: 99%
“…A study conducted in Paraná, Brazil, confirmed that the types and levels of concentrations of compounds produced by five study species were the same in the soils of the seasonal semideciduous forest and the lowland ombrophilus dense forest, although the levels of these compounds differed between the sites. The type of tannin of Schinus terebinthifolius also differed between these forests [37].…”
Section: Correlation Among Soil Microorganisms and Secondary Compoundsmentioning
confidence: 96%